2020
DOI: 10.1088/1755-1315/476/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural fibers on the soil compaction characteristics

Abstract: Clay soils are considered as a problematic soil in term of water absorption rate. The ideas of soil improvement method had been widely used to modify the physical and mechanical properties of clay soil. This study aims to identify the optimum percentage mixing of natural fibers in influencing the compaction characteristics. X – ray fluorescent test (X-RF) and Standard Proctor test has been performed to determine the chemical composition of natural fibers and compaction characteristics of soil samples. Natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Perera et al (2022) investigated that the maximum dry density of stabilized cohesive soil increases insignificantly with increasing crushed waste glass content (by a maximum of 5%), whereas the optimum water content decreases (by a maximum of 14%). Bawadi et al (2020) reported that the MDD and OWC parameters depend not only on the content of natural fiber but also on their type. The researchers determined the highest maximum dry density at 0.5% banana fiber content.…”
Section: Maximum Dry Density and Optimum Water Content Of Waste-stabi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Perera et al (2022) investigated that the maximum dry density of stabilized cohesive soil increases insignificantly with increasing crushed waste glass content (by a maximum of 5%), whereas the optimum water content decreases (by a maximum of 14%). Bawadi et al (2020) reported that the MDD and OWC parameters depend not only on the content of natural fiber but also on their type. The researchers determined the highest maximum dry density at 0.5% banana fiber content.…”
Section: Maximum Dry Density and Optimum Water Content Of Waste-stabi...mentioning
confidence: 99%
“…The lowest value of the MDD parameter was found at 1% kenaf fiber content and it was even lower than determined for untreated clayey soil. Bawadi et al (2020) investigated that the optimum water content increases with increasing fiber content for all types of natural fibers added to clayey soils, however, the most significant change in OWC was observed with the addition of kenaf fibers. The addition of sawdust reduces the maximum dry density by 10% and increases the optimum water content by 10% at a sawdust content of 7% (Niyomukiza et al, 2020).…”
Section: Maximum Dry Density and Optimum Water Content Of Waste-stabi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The result of these tested samples is to be used in sample preparation for the California bearing ratio tests. The results were tabulated in Table 4.The maximum dry density of the samples of the soil increases with the addition of fibres and the optimum moisture content varies between 12% and 10% [14].The gradual decrease in Optimum moisture content indicates that the adsorption of water by the fine-grained soil is reduced. The results were plotted in Fig 2 . .…”
Section: Unconfined Compressive Strength Test (Ucc)mentioning
confidence: 99%
“…Synthetic fibres are light grey. Table2shows the properties of natural and synthetic fibres from Mahuyu Ghosh et.al.,(2014)[14] Properties of fibres(after Mahuya Ghosh 2009)…”
mentioning
confidence: 99%